(untitled) (Doctor Virtualis, 2024)
Literature tries to give order to the disorder of life and history. This is why it happens that a fictional character like Robin Hood is too lover of freedom and disorder to be merely literary, and so generations of scholars have sought traces of him in the real events of English history. The tradition of folk ballads has invaded theatre and literature, giving the collective imagination throughout Europe the illusion that disorder can be planned.